(untitled) (Revista Rupturas, 2023)
Our Costa Rican legislation describes the theme of the objects and subjects of Law. The Costa Rican Civil Code, topics such as real estate, personal property and the individual, The Family Code, describes the family unit, the interest of children and minors. However, it has been taking place in Latin America, an issue that entails legal protection towards domestic animals, being able to call them as subjects or percos, In the present article, the context of legal protection of people and things will be addressed, Subsequently, Relevant elements will be delved into, both nationally and internationally. Finally, the possible reforms in the aforementioned normative bodies will be described, regarding the perverse ones and/or the subjects of Law.